2022
DOI: 10.1093/jac/dkac327
|View full text |Cite
|
Sign up to set email alerts
|

Loss of outer membrane protein A (OmpA) impairs the survival of Salmonella Typhimurium by inducing membrane damage in the presence of ceftazidime and meropenem

Abstract: Objectives Salmonella enterica serovar Typhimurium is one of the significant non-typhoidal Salmonella serovars that causes gastroenteritis. The rapid development of antimicrobial resistance necessitates studying new antimicrobials and their therapeutic targets in this pathogen. Our study aimed to investigate the role of four prominent outer membrane porins of S. Typhimurium, namely OmpA, OmpC, OmpD and OmpF, in developing resistance against ceftazidime and meropenem. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“…63 Ray et al 64 proposed that the decrease in the expression of ompD, ompC, and ompF upon exposure to altered stress conditions leads to the development of resistance in S. Typhimurium. A similar study was conducted by Chowdhury et al, 65 wherein deletion of ompA, ompC, ompD, and ompF genes in S. Typhi showed significant changes in antibiotic susceptibility toward ceftazidime and meropenem. Some studies have also reported the development of carbapenems resistance due to porin loss in addition to the production of ESBLs in S. Typhimurium.…”
Section: Resistance In Salmonellasupporting
confidence: 65%
“…63 Ray et al 64 proposed that the decrease in the expression of ompD, ompC, and ompF upon exposure to altered stress conditions leads to the development of resistance in S. Typhimurium. A similar study was conducted by Chowdhury et al, 65 wherein deletion of ompA, ompC, ompD, and ompF genes in S. Typhi showed significant changes in antibiotic susceptibility toward ceftazidime and meropenem. Some studies have also reported the development of carbapenems resistance due to porin loss in addition to the production of ESBLs in S. Typhimurium.…”
Section: Resistance In Salmonellasupporting
confidence: 65%
“…Salmonella typhimurium (STM), one of the leading causes of self-limiting gastroenteritis and diarrhea in humans, 6 , 7 has been used as a model system in the present study. However, the proposed experimental methodology is suitable for investigating any naturally dried bacterial droplets.…”
Section: Introductionmentioning
confidence: 99%
“…In a bacterium, the resistome refers to all the resistance-associated genes (Wright, 2007). It includes the proto-resistance genes AMR in S. Typhimurium (Chowdhury et al, 2022;Roy Chowdhury et al, 2022).…”
Section: S Typhi Virulence Overlaps With Amrmentioning
confidence: 99%
“…Our laboratory has extensively characterized the role of outer membrane protein A (OmpA) in combating innate immune responses and AMR in S . Typhimurium (Chowdhury et al., 2022; Roy Chowdhury et al., 2022).…”
Section: Mechanisms Of Drug Resistance In Salmonellamentioning
confidence: 99%